Finite element simulation of high-speed finish milling of SKD11 hardened steel based on modified constitutive equation. Issue 1 (1st January 2018) - Dewen, Tang; Cong, Peng; Jiayu, Zhang
Abstract: High precision parts have been widely used in automobile, aerospace, medical and other fields. Conventional machining methods are difficult to meet the requirements of the high-quality requirements of components, including shape precision, dimensional accuracy, surface finish and surface integrity. Using milling instead of grinding can significantly improve machining efficiency of ultra-precision parts for difficult cut materials, especially high hardness SKD11 hardened steel. To improve the surface quality and the processing surface integrity of the parts, high-speed milling (HSM) can be able to meet the high-quality requirements of components. However, the quality of finish HSM is difficult to control through experiments. Therefore, the modified flow stress model of SKD11 hardened steel based on SHPB experimental is adopted to simulate the high-speed finish milling in this paper. The effect of cutting parameters on chip formation, cutting temperature, stress and cutting force of SKD11 are analyzed. Compared with the experimental data of cutting force of different cutting parameters, the simulation results are the same as the measured data. The results show that the model can predict the performance of the SKD11 high-speed finish milling process accurately.